TGF‐β regulates the release of breast cancer cell‐derived extracellular vesicles and the sorting of their protein cargo by downregulating RAB27B expression - Chao Li; Agustin Enciso‐Martinez; Roman I. Koning; Mona Shahsavari; Peter ten Dijke (Journal of Extracellular Vesicles)
Abstract Extracellular vesicles (EVs) are important mediators of intercellular communication in the tumour microenvironment. The cytokine transforming growth factor‐β (TGF‐β) facilitates cancer progression via EVs secreted by cancer cells, which act on recipient cells in the tumour microenvironment. However, the mechanisms of how TGF‐β affects cancer cell EV release and composition are incompletely understood. Here, we systematically investigate the effects of TGF‐β on the release and protein composition of EVs from breast cancer cells. TGF‐β suppresses the transcription of RAB27B mediated by SMAD3 and thereby hampers EV release. Using click chemistry and quantitative proteomics, we found that TGF‐β increases the quantity of protein cargo and changes the composition of EVs by downregulating RAB27B expression. The recomposed EVs, induced by TGF‐β or RAB27B depletion, inhibit CD8+ T cell‐mediated breast cancer killing. Our findings reveal the critical roles of TGF‐β and RAB27B in cancer development by regulating EV release and composition and thus provide potential targets to improve cancer immunotherapy.